2021
DOI: 10.19173/irrodl.v22i4.6283
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Open and Distance Learning Reform at the National University of Lesotho: A Managerial Perspective

Abstract: This study investigated how open and distance learning (ODL) reform was managed within the Institute of Extramural Studies (IEMS), at the National University of Lesotho (NUL). The reform was introduced during the 2017/18 academic year with first-year programmes in three departments: (a) Adult Education; (b) Business and Management Development; and (c) Research, Evaluation, and Media. The study employed interviews and analysis of institutional documents as data collection techniques. Interviews were held with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…Provision of distance education requires a different funding model from campus-based provision and institutions need to develop an appropriate business model before launching distance courses or they might run into financial challenges (Nketekete and Mojafela 2021). It is suggested that in some contexts there might be a need for a trade-off between scope and scale of provision (Zhang and Worthington 2017).…”
Section: Finances/economicsmentioning
confidence: 99%
“…Provision of distance education requires a different funding model from campus-based provision and institutions need to develop an appropriate business model before launching distance courses or they might run into financial challenges (Nketekete and Mojafela 2021). It is suggested that in some contexts there might be a need for a trade-off between scope and scale of provision (Zhang and Worthington 2017).…”
Section: Finances/economicsmentioning
confidence: 99%
“…In remote learning, students are physically distant from their instructors and require internetconnected digital devices, such as laptops, tablets, desktop computers, and smartphones. Remote learning is delivered synchronously (lecturers and students are online at the same time) or asynchronously (lecturers and students are online at different times and locations if internet access is poor for either party) (Nketekete et al, 2021;Syahruddin et al, 2021). There are various means of conveying remote learning, which range from traditional take-home materials (books) to modern online and digital resources.…”
Section: Introductionmentioning
confidence: 99%